SAT-LB064 Mitotane Induces Autophagy: A Mechanism to Promote Chemoresistance in Adrenocortical Carcinoma - Tompkins, Kenneth (J Endocr Soc, 2019)
Adrenocortical carcinoma (ACC) is an orphan malignancy with dismal survival rates. Although recent large genomic studies have shed insight into underlying molecular mechanisms, there are currently no targeted therapies available. Autophagy is an important cellular process to promote survival in a low nutrient tumor microenvironment or in the setting of physiologic stimuli such as endoplasmic reticulum stress (ER stress). In some settings, autophagy can result in drug resistance to cytotoxic chemotherapies and tyrosine kinase inhibitors. The role of autophagy in ACC has not been well characterized. Previous research in H295R ACC cells has shown that mitotane, the only FDA approved drug for ACC, promotes cell death in part through ER stress. Since autophagy has been shown to promote resistance to ER stress-mediated cell death, we hypothesized that autophagy may be activated in ACC cells as a compensatory mechanism, promoting cell survival in the face of mitotane treatment. CU-ACC2 cells demonstrated functional autophagy in response to Earle’s Balanced Salt Solution (EBSS), a potent stimulant of autophagy, indicated by a significant increase in the autophagy mediator LC3-II, as detected by immunoblot and enhanced autophagic flux detected by flow cytometry in cells expressing a tandem LC3-mCherry-GFP construct. To test if mitotane induces ER stress in our novel cell lines, qPCR was performed examining the expression of several ER stress pathway components including CHOP and XBP1 cleavage. In agreement with previous data in H295R ACC cells, there was significant cleavage of XBP1 and increased expression of CHOP in response to mitotane treatment in CU-ACC2, confirming ER stress induction. Mitotane also induced autophagy, as measured by LC3 detection by immunoblot as well as flow cytometry. ER stress induction was detected as early as 6 hours, while autophagy induction occurred later and peaked at 24 hours suggesting that ER stress precedes induction of autophagy in ACC cells. A functional effect of autophagy induction after mitotane treatment was demonstrated by treatment with mitotane with or without the autophagy inhibitor, chloroquine. Significantly more cleaved PARP, suggesting greater apoptosis, was detected after 24 and 48 hours of treatment with combination therapy than with than with either treatment alone. Together, these data suggest that mitotane activates ER stress to trigger apoptosis, but this treatment also activates autophagy, which abrogates the toxic effects. Thus, inhibition of the autophagy pathway may be a potential therapeutic adjunct to mitotane therapy in patients with ACC. Funding: VA Merit, Cancer League of Colorado, NIH K08, NIH R01 to AT. Unless otherwise noted, all abstracts presented at ENDO are embargoed until the date and time of presentation. For oral presentations, the abstracts are embargoed until the session begins. Abstracts presented at a news conference are embargoed until the date and time of the news conference. The Endocrine Society reserves the right to lift the embargo on specific abstracts that are selected for promotion prior to or during ENDO.